Perlindungan Hukum Terhadap Perempuan Korban Pembunuhan Berbasis Femisida Di Indonesia - Amelia, Fernanda; Kusnadi, Sekaring Ayumeida (Universitas Gorontalo, 2025)
The women in Indonesia often become victims of gender-based violence, one of which takes the form of femicide, that is, the murder of women committed for gender-related reasons. This phenomenon raises important issues regarding legal protection for women. This research aims to analyze the forms of legal protection for women victims of femicide in Indonesia, as well as to identify violations that occur within the context of existing legal regulations. The method used in this research is normative juridical, with a legislative approach, which examines relevant legislation, Such as the Criminal Code (KUHP), Law No. 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT), Law No. 12 of 2002 concerning Sexual Violence Crimes (TPKS), and Law No. 7 of 1984 concerning the Ratification of the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW). This research utilizes primary legal materials obtained through literature study and documentation to examine how these regulations protect women victims of femicide. The results of this study are expected to provide insights into the weaknesses and opportunities in enhancing legal protection for women in Indonesia.